Adaptação do código Geant4 para conversão de imagens DICOM em phantom virtual - Silva, Fabrício Loreni da (2013)
This work presents the adaptation of the Geant4 code for converting DICOM (Digital Imaging and Communications in Medicine) images of a skull, obtained in conventional tomography (CT), into a virtual anthropomorphic phantom. The work was based on the medical example named "Dicom Code" provided by the developers of the code Geant4. During the execution, restructurings using the "Dicom Code" example were made to achieve the direct conversion of tomographic images into a virtual phantom. All the steps referring to nuclear physical events were removed. The file DicomHandler.cc was reformulated in order to avoid the pixels compression of the CT image. The CT images of a physical polyethylene (PEAD) phantom with acrylic core and a real human skull were then converted into virtual phantoms for the code Geant4. The results showed that with this code, it may be possible the reconstruction of anatomical areas with complex geometries, based on the use of real tomographic images.